Guillain-Barré syndrome after adoptive cell therapy with tumor-infiltrating lymphocytes. Issue 2 (26th August 2020) - Orcurto, Angela; Hottinger, Andreas; Wolf, Benita; Navarro Rodrigo, Blanca; Ochoa de Olza, Maria; Auger, Aymeric; Kuntzer, Thierry; Comte, Denis; Zimmer, Virginie; Gannon, Philippe; Kandalaft, Lana; Michielin, Olivier; et al.
Abstract : Background: Adoptive cell therapy (ACT) using tumor-infiltrating lymphocytes (TILs) is a promising experimental immunotherapy that has shown high objective responses in patients with melanoma. Current protocols use a lymphodepletive chemotherapy before infusion of ex vivo expanded TILs, followed by high-dose interleukin-2 (IL-2). Treatment-related toxicities are mainly attributable to the chemotherapy regimen and to the high-dose IL-2 and are generally reversible. Neurological side effects have rarely been described. Nevertheless, due to improvements in cell production techniques and due to combinations with other immunomodulating molecules, side effects not previously described may be encountered. Case presentation: We report the case of a 53-year-old heavily pretreated patient with melanoma who developed Guillain-Barré syndrome (GBS) 19 days after ACT using autologous TILs, given in the context of a phase I trial. He presented with dorsal back pain, unsteady gait and numbness in hands and feet. Lumbar puncture showed albuminocytological dissociation, and nerve conduction studies revealed prolonged distal motor latencies in median, ulnar, tibial and peroneal nerves, compatible with a GBS. The patient was treated with intravenous immunoglobulins and intensive neurological rehabilitation, with progressive and full recovery at 21 months post-TIL-ACT. Concomitant to the onset of GBS, a cytomegalovirus reactivation on immunosuppression was detected and considered as the most plausible cause of this neurological side effect. Conclusion: We describe for the first time a case of GBS occurring shortly after TIL-ACT for melanoma, even though we could not identify with certainty the triggering agent. The report of such rare cases is of extreme importance to build on the knowledge of immune cellular therapies and their specific spectrum of toxicities.